The Jewish Bible and the Christian Bible an introduction to the history of the Bible - Barrera, Julio Trebolle (Leiden, Germany Brill, 1998)
Includes bibliographical references and index.
Originally published in Spanish as La Biblia judia y la Biblia cristiana
Keywords: Bible -- history